Quantitative fluorescence in situ hybridization for investigation of telomere length dynamics in the pituitary gland using samples from 128 autopsied patients. (August 2018) - Hiraishi, Naoki; Terai, Masanori; Fujiwara, Mutsunori; Aida, Junko; Izumiyama-Shimomura, Naotaka; Ishikawa, Naoshi; Tomita, Ken-ichiro; Matsuda, Yoko; Arai, Tomio; Takubo, Kaiyo; Ishiwata, Toshiyuki
Highlights: We analyzed telomere lengths in the pituitary gland, glandular cells, and pituicytes. Telomeres in the adenohypophysis shortened with aging, but those of pituicytes did not. Pituicyte telomeres were significantly longer in women than in men. Telomeres tended to be longer in individuals in their 80s and 90s than in those in their 70s, lending support for the contention that humans with longer telomeres have a longer lifespan. Our findings shed light on the biology of the pituitary gland in terms of telomere length dynamics, and will contribute to the development of bioengineered hormone-producing cell replacement strategies and regenerative therapies. Abstract: In order to investigate the population dynamics of telomere status, we measured the telomere lengths of glandular cells in the adenohypophysis (AH) and pituicytes, a type of glial cell, in the neurohypophysis (NH) of 128 autopsied humans (65 men, 63 women, 0 and 102 years) using our original quantitative fluorescence in situ hybridization (Q-FISH) method. Telomeres in the AH shortened with aging in both men and women, but those of pituicytes did not. Pituicyte telomeres were significantly longer in women than in men. The data suggest that telomeres shorten with age in the AH, whereas those in pituicytes maintain a constant length throughout life. Comparison of pituicyte telomere lengths among 5 generations, <18, 18–69, 70–79, 80–89, and> 90 years, revealed a tendency for telomeres to be longer in individuals in their 80 s and 90 s than in those in their 70 s. These findings lend support to the widely held notion that humans with longer telomeres may have a longer life span, and shed light on the biology of pituitary gland in terms of telomere length dynamics, as well contributing to the development of bioengineered hormone-producing cell replacement strategies and regenerative therapies.